2017
DOI: 10.1186/s40575-017-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Population characteristics of golden retriever lifetime study enrollees

Abstract: BackgroundStudying cancer and other diseases poses a problem due to their protracted and multifactorial nature. Prospective studies are useful to investigate chronic disease processes since collection of lifestyle information, exposure data and co-incident health issues are collected before the condition manifests. The Golden Retriever Lifetime Study is one of the first prospective studies following privately-owned dogs throughout life to investigate the incidence and risk factors for disease outcomes, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Such observations mean that genetic and environmental risk factors for cancer may be identified in smaller prospective studies, taking less time, than would be necessary in people. The leading cause of death in Golden retrievers is hematopoietic malignancy (86), and in 2012 a prospective study of >3,000 Goldens, enrolled at age 2 or younger, was undertaken (87). The goal of this study was to collect environmental and biological data for correlation with the future diagnoses of malignancy and other diseases.…”
Section: Exploiting Breed-specific Diseases For Prevention and Diseasmentioning
confidence: 99%
“…Such observations mean that genetic and environmental risk factors for cancer may be identified in smaller prospective studies, taking less time, than would be necessary in people. The leading cause of death in Golden retrievers is hematopoietic malignancy (86), and in 2012 a prospective study of >3,000 Goldens, enrolled at age 2 or younger, was undertaken (87). The goal of this study was to collect environmental and biological data for correlation with the future diagnoses of malignancy and other diseases.…”
Section: Exploiting Breed-specific Diseases For Prevention and Diseasmentioning
confidence: 99%
“…In four years, the GRLS has amassed a sample set of over 3,000 Golden Retrievers, complete with annual biological samples and standardized phenotype data collection from owners and veterinarians (Simpson et al, 2017), and represents a one-of-a-kind dataset for genomic analysis. Here, we combine detailed reproductive data gathered on 93 GRLS participants with high-density SNP genotyping.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 35% of farm dogs in the current study were covered by an insurance policy. This is higher than the 20% insurance coverage reported in Golden retrievers enrolled in a longitudinal study in the United States [36]. Additionally, in Australia it has been estimated that about 7% of dog owners have pet insurance [37], however it has been suggested that this might be an underestimate [38].…”
Section: Discussionmentioning
confidence: 86%